The Tools of Learning to Write Based On Family Zone Readiness In Online Learning - Dian Indihadi; M. Sameer Babu; Fahmi Qodrul Asphar; Risnandar Sudarman (Journal of Future Education, 2023)
This study focused on the readiness of family zone in supporting online learning for the development of learning to write tools in primary school. There were some focuses on the readiness of family zone to support online learning, such as: (1) learning facilities, (2) understanding of lesson content area, and (3) guiding the process of learning to write. The study was carried out by using a “Design Based Research” (DBR) approach in Mugarsari 1 primary school, Tamansari district, Tasikmalaya city. The result showed that the readiness of the family environment in online learning in the development of learning tools, especially for determining (1) the achievement of learning outcomes, (2) the scope of teaching materials, and (3) writing learning strategies. In this learning, writing as a skill was developed through the stages of (1) Pre-writing, (2) “Drafting”, (3) Revising, (4) Editing, and (5) Publishing with the “Brain Storming” and “Mind Mapping” strategies.